Answer:
1. y=(x-1)(2x+3)(x-4)
x-intercept: 0=(x-1)(2x+3)(x-4)
x-1=0
2x+3=0
x-4=0
[(1,0),(-3/2,0),(4,0,)]
y-intercept: y=(0-1)(2(0)+3)(0-4)
y=(-1)(3)(-4)
[(0,12)]
2. y= -(x+1)² (x-2)²
x-intercept: 0= -(x+1)² (x-2)²
(x+1)²=0
(x-2)²=0
[(-1,0),(2,0)]
y-intercept: y= -(0+1)² (0-2)²
y= -(1)(4)
[(0,-4)]
3. y=x(x-1)(x-2)(x+3)
x-intercept: 0=x(x-1)(x-2)(x+3)
x=0
x-1=0
x-2=0
x+3=0
[(0,0),(1,0),(2,0),(-3,0)]
y-intercept: y=0(0-1)(0-2)(0+3)
[(0,0)]
4. y= -(x+3)(x-2)(x-4)(x+1)
x-intercept: 0= -(x+3)(x-2)(x-4)(x+1)
x+3=0
x-2=0
x-4=0
x+1=0
[(-3,0),(2,0),(4,0),(-1,0)]
y-intercept: y=-(0+3)(0-2)(0-4)(0+1)
y=-(3)(-2)(-4)(1)
[(0,-24)]
5. y=(x+1)(x-1)(x+5)(x-5)
x-intercept: 0=(x+1)(x-1)(x+5)(x-5)
x±1=0
x±5=0
[(1,0),(-1,0),(5,0),(-5,0)]
y-intercept: y=(0+1)(0-1)(0+5)(0-5)
y=(1)(-1)(5)(-5)
[(0,25)]